Sparsity based Single Object Tracking - Abraham, Glincy; Narayanankutty, K.A.; Soman, K.P. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Object tracking has importance in various video processing applications like video surveillance, perceptual user interface driver assistance, tracking etc. This paper deals with a new tracking technique that combines the dictionary based background subtraction along with sparsity based tracking. The speed and performance challenges faced during the sparsity based tracking alone are addressed, as it is based on a background subtraction preprocessing and local compressive tracking. It also overcomes the challenges faced by the traditional techniques due to illumination variation, pose and shape change of the object. Output of the proposed technique is compared with that of compressive tracking technique.